Can Threat Increase Support for Liberalism? New Insights Into the Relationship Between Threat and Political Attitudes. Issue 1 (January 2020) - Eadeh, Fade R.; Chang, Katharine K.
The extant literature demonstrates that exposure to threat almost always increases support for political conservatism. But can threat increase the support for political liberalism? The current article provides evidence that threat can increase the aspects of political liberalism. Across three experiments, we find that experimentally manipulated threats to health-care access (Experiment 1, N = 558), pollution (Experiment 2, N = 184), and corporate misconduct (Experiment 3, N = 225) produced increased support for components of liberalism. These findings fill a notable gap in the literature, broadening larger theoretical discussions of threat as a psychological construct and current understandings of experimentally manipulated attitudinal change.